Novel investigational drugs active as single agents in multiple myeloma. (3rd June 2017) - D'Agostino, Mattia; Salvini, Marco; Palumbo, Antonio; Larocca, Alessandra; Gay, Francesca
ABSTRACT: Introduction : Multiple myeloma (MM) is a hematologic malignancy characterized by proliferation of malignant plasma cells. patient outcome has improved markedly over the last decades due to the introduction of novel therapeutic agents such as bortezomib, thalidomide and lenalidomide. However, MM still remains largely incurable and patients eventually become refractory to available treatments. To address this unmet medical need, a variety of new molecules are currently being developed in preclinical models and/or are being investigated in clinical studies. Areas covered : We summarized available data on new investigational drugs showing anti-myeloma single-agent activity and that might have a role in the future therapeutic armamentarium against MM. Besides their single-agent activity, the synergic potential of these new agents with the currently approved drugs will be pivotal in their integration into consolidated MM backbone therapies. The drugs discussed include alkylators, new proteasome inhibitors, novel anti-CD38 monoclonal antibodies, Bcl-2 inhibitors, Cyclin-Dependent-Kinase inhibitor, Kinesin-spindle protein inhibitors, MEK1/2 inhibitors, AKT inhibitors and PIM-Kinase inhibitors. Expert opinion : Isatuximab, oprozomib, melflufen, venetoclax and filanesib seem to be the most promising agents with single agent activity. Nevertheless, lack of clinical activity as single agent does not imply clinical inefficacy in combination treatments.